Overview of work-related cancers in Europe (Paris, 2002)
"This survey deals with the types of cancers which can be recognised as work-related in 14 countries. It also endeavours to provide significant statistics, since it inventories claims for recognition and recognised cases of work-related cancers over the period 1998-2000."